Imaging in ESC clinical guidelines: chronic coronary syndromes - Saraste, Antti; Barbato, Emanuele; Capodanno, Davide; Edvardsen, Thor; Prescott, Eva; Achenbach, Stephan; Bax, Jeroen J.; Wijns, William; Knuuti, Juhani (European Heart Journal - Cardiovascular Imaging, 2019)
The European Society of Cardiology (ESC) has recently published new guidelines on the diagnosis and management of chronic coronary syndromes (CCS). The 2019 guideline identified six common clinical scenarios of CCS defined by the different evolutionary phases of coronary artery disease (CAD), excluding the situations in which an acute coronary event, often with coronary thrombus formation, dominates the clinical presentation. This review aims at providing a summary of novel or revised concepts in the guidelines together with the recent data underlying the major changes on the use of cardiac imaging in patients with suspected or known CCS. Based on data from contemporary cohorts of patients referred for diagnostic testing, the pre-test probabilities of CAD based on age, sex and symptoms have been adjusted substantially downward as compared with 2013 ESC guidelines. Further, the impact of various risk factors and modifiers on the pre-test probability was highlighted and a new concept of 'Clinical likelihood of CAD' was introduced. Recommendations regarding diagnostic tests to establish or rule-out obstructive CAD have been updated with recent data on their diagnostic performance in different patient groups and impact on patient outcome. As the initial strategy to diagnose CAD in symptomatic patients, non-invasive functional imaging for myocardial ischaemia, coronary computed tomography angiography or invasive coronary angiography combined with functional evaluation may be used, unless obstructive CAD can be excluded by clinical assessment alone. When available, imaging tests instead of the exercise electrocardiogram are recommended when following the non-invasive diagnostic strategy.
CRIS-Team Scopus Importer:2019-10-29
Keywords: cardiac magnetic resonance; coronary artery disease; coronary computed tomography angiography; echocardiography; positron emission computed tomography; single-photon emission computed tomography